Tax audit and examination of electronic accounting information systems: proposed model / Applied research at the General Tax Authority (Journal of Accounting and Financial Studies ( JAFS ), 2021)
Technology is one of the important influences in the development of professions in general and the profession of tax auditing and examination in particular because of the importance of this section in the General Tax Authority because of the service it provides is auditing the financial accounts provided to the department by the taxpayers to ensure the correctness of revenue and the achievement of tax justice. Where the research aims at the importance of using electronic accounting information systems in developing the work of the Tax Audit and Examination Department, to reduce the difficulties that the department may be using using manual systems, which is the need for time and effort to accomplish it, and to develop methods and procedures for auditing and examination using electronic accounting information systems, and that is By designing electronic programs and systems that help in carrying out work quickly, with greater accuracy, and with less effort, and to achieve the research goal, an electronic system for tax audit and examination was designed using the Microsoft Excel spreadsheet program (for the purpose of developing A new system that is based on modern technology in order to assist in carrying out the work of electronic auditing and examination of financial accounts. One of the most important findings of this research is the possibility of achieving the goal of accuracy and speed in implementing financial audits electronically, by employing modern methods and procedures that work in An electronic audit environment One of the most important recommendations of the research is the necessity of developing the work of the department through electronic accounting programs and systems that help in conducting electronic data audits and developing the skills of the auditing and tax examination department employees through their participation in training courses that provide Do they have to practice electronic auditing work, as it requires him to understand and study well the system through which the data is audited electronically in addition to the necessity of providing the Tax Audit and Examination Department with data electronically or printed on tablets, and to take advantage of technology advantages by using modern methods and procedures that help the examiner to accomplish his work in a manner Best.